(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
The optimized conditions for measuring thiocyanate by extracting through formation of ion pair with thionine basic dye (Lauth’s violet) have been determined by means of spectrophotometric method. Thionine was extracted at the presence of thiocyanate and has absorption spectrum at the 600 nm wavelength. The increase in the intensity of absorption takes place, because of thionine and thiocyanate ionic associate (ion pair) formation and transfer to the organic phase (extraction). In this investigation all parameters were kept constant except the one to be optimized. The optimal conditions for the determination of thiocyanate ion by means of thionine are the following: solvent – methylisobutyl keton; [thionine] – 1.566·10–4 mol/L; medium acidity – pH 6–7; temperature – 30°C; ionic strength – 0.0; extraction process duration – 240 s.